TAAR1 Agonist Ulotaront Improves Glycemic Control and Reduces Body Weight in Rodent Models of Diabetes, Obesity, and Iatrogenic Weight Gain. (April 2023) - Dedic, Nina; Jones, Philip G.; Hajos-Korcsok, Eva; Synan, Colleen; Wu, Serena; Anacker, Christoph; Vickers, Steve P.; Hecksher-Sørensen, Jacob; Zeni, Courtney; Milanovic, Snezana; Hopkins, Seth C.; Bristow, Linda J.; et al.
Abstract: Introduction: Preclinical evidence has identified the trace amine-associated receptor 1 (TAAR1) as a novel regulator of metabolic control. Ulotaront is a TAAR1 and 5-HT1A agonist currently in Phase 3 clinical trials for the treatment of schizophrenia. Here we summarize preclinical results assessing the effects of ulotaront on weight and metabolic parameters. Methods: Effects of ulotaront administration were evaluated on oral glucose tolerance (oGTT), gastric emptying, and in rodent models of weight gain (high-fat diet [HFD]-, corticosterone-, and olanzapine-induced). Results: Following 15-day oral administration of ulotaront, rats on HFD showed dose-dependent reduction in body weight, food intake, and liver triglyceride content compared to controls. In addition, a more rapid reversal of olanzapine-induced weight gain and food intake was observed in rats switched to ulotaront (vs. vehicle). Consistent with weight-lowering effects in rats, chronic ulotaront treatment normalized corticosterone-induced weight gain in mice. Assessment of oGTT showed a dose-dependent reduction of glucose excursion in response to acute ulotaront administration in naive and diabetic db/db mice. Ulotaront administration also delayed gastric emptying in mice—a likely mechanism driving reductions in glucose excursions during the oGTT. Whole-brain c-fos imaging of ulotaront-treated mice revealed increased neuronal activity in several brain regions associated with regulation of food intake and metabolic signals. Conclusions: The data indicate that ulotaront not only lacks metabolic liabilities typically associated with antipsychotics but can reduce body weight and improve glucose tolerance in rodent models. The underlying mechanisms may include TAAR1-mediated peripheral effects on glucose homeostasis and/or direct modulation of homeostatic and hedonic neurocircuits regulating energy balance. The beneficial metabolic effects of ulotaront may suggest a substantially improved risk-benefit profile compared to established antipsychotics. Funding: Sunovion Pharmaceuticals Inc. and Otsuka Pharmaceutical Development & Commercialization, Inc.